The Role of Self-Efficacy in Job Crafting with Person Job-Fit as a Mediating Variable - Elsuza Pahlaweni; Adi Rahmat; Agus Seswandi (Lembaga Riset dan Inovasi Al-Matani, 2025)
In today's increasingly competitive and dynamic work environment, organizations need employees who can not only carry out formal tasks but also proactively adapt and modify their work. This is known as Job Crafting. Through Job Crafting, employees can improve the fit between themselves, work, and the organization, and encourage positive outcomes such as motivation, job satisfaction, and performance. The purpose of this research is to determine the role of self-efficacy in job crafting. Person Job-fit as a Mediating Variable. This research is a type of quantitative research with a causality research design and the population is State Civil Apparatus and Honorary Staff at the Investment and One-Stop Integrated Services Office of Indragiri Hilir Regency. with a sample of 65 people. Data collection techniques using questionnaires and distribution using Google Form. The data analysis tool in this research is Structural Equation Modeling (SEM) processed using SmartPLS 3.2.9 for data processing. The results of this research are that Self Efficacy has a positive and significant effect on Person Job Fit, Self Efficacy has a positive and significant effect on Job Crafting, Person Job Fit has a positive and significant effect on Job Crafting and Self Efficacy has a positive and significant effect on Job Crafting through Person Job Fit.